PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN DAMPAKNYA TERHADAP PRESTASI BELAJAR MATEMATIKA PADA MATERI BANGUN RUANG SISI DATAR DI SMP NEGERI 2 LOLAYAN - Mohammad Fahrul Muhfito; Patricia V.J. Runtu; Ichdar Domu (Universitas Nias Raya, 2026)
Weak mathematics mastery among learners is a recurring issue in education, particularly in schools that still rely on one-way instruction. This study focused on determining whether there is a significant disparity in mathematics learning achievement between Grade VIII students using the Numbered Heads Together (NHT) cooperative approach and those receiving direct instruction, specifically on the topic of Flat-Sided Three-Dimensional Shapes. A quasi-experimental pretest-posttest control group method was used. Through random procedures, Class VIII B was designated as the experimental class and Class VIII C as the comparison class, with 16 students each. The evaluation instrument consisted of essay questions that had been tested for suitability. Data processing was conducted through an independent-samples t-test (α = 0.05). A t-value of 9.60 was obtained, exceeding ttable = 1.697, so the null hypothesis was successfully rejected. The final mean of the experimental class reached 76.00 compared to 48.25 in the comparison class, indicating that NHT implementation significantly elevates students' mathematics achievement.